Hunt for Nazis : South America's dictatorships and the prosecution of Nazi crimes - Stahl, Daniel (Studies of the NIOD Institute for War, Holocaust and Genocide Studies., 2018)
Hunt for Nazis is the first comprehensive account of the post-1945 efforts to bring Nazi war criminals who had escaped to South America to justice. The author shows that the Nazi hunt -- which resulted in spectacular cases like the kidnapping of Adolf Eichmann -- should not only be understood as part of the afterlife of the Third Reich, but that it also became an integral aspect of dealing with repression at the hands of authoritarian regimes in South America. Dissidents and human rights activists assumed that the escaped Nazi perpetrators and collaborators continued to be involved in violent crimes in the service of these new dictatorships.